Social Entrepreneur Ship: Inovasi dan Tantangannya di Era Persaingan Bebas - Agung Surya Dwianto (Majalah Ilmiah Bijak, 2018)
In many countries, especially in developing countries, there are many social problems that need to be resolved. The high level of poverty and unemployment, the lack of available health facilities, or the low quality of existing education, is an acute problem that becomes a tough domestic work for a developing country's government. Given the current global conditions, where free competition is inevitable, it certainly adds to the long list of strategies that the government must take to tackle various social problems. The government can not struggle and work alone in dealing with the complexity of the existing problems, it is certainly necessary for the active role of all elements of the society so that the problems that whack, can unravel and be solved. One step that can be taken by the government in order to empower and protect the people in the era of free competition is to support, develop, and multiply the existence of social entrepreneurship. Social entrepreneurship has the potential to provide some social solutions that affect a country.This paper shows the concept of social entrepreneurship as historical background, characteristics, challenges faced and business model of social entrepreneurship in order to overcome various social problems that can have a positive impact on economic development.